Lower proteinuria is better for patients with IgA nephropathy: a systematic review - Shah, Ankit; Maski, Manish; Egbuna, Ogo; Longstaff, Whitney; Stricker-Shaver, Janice; Barber, Beth (Frontiers in Nephrology, 2026)
BackgroundProteinuria is a well-established and recommended biomarker for disease activity in patients with IgAN. In the most recent version of the KDIGO guideline, the target level of proteinuria changed from < 1.0 g/day to < 0.5 g/day. The objective of this systematic literature review (SLR) is to identify, synthesize, and critically evaluate the evidence from peer-reviewed publications that inform the significance of achieving different proteinuria levels.MethodsWe searched PubMed and Embase (2005-2025) for studies in adult patients diagnosed with IgAN that examined the relationship between proteinuria measured by any method (e.g., uPCR, 24-hour protein excretion) and key kidney outcomes. The review used an a priori protocol following established methodological guidance for systematic reviews. Additionally, the quality of all studies included in the SLR was assessed based on standardized appraisal tools. The evidence was narratively synthesized reporting frequencies and percentages.ResultsTwenty-one unique studies were included (representing 13,006 patients with IgAN). The studies captured in the SLR were mostly observational and they encompassed diverse patient populations, timing of proteinuria assessment, methods of proteinuria measurement and classification, and clinical management strategies, reflecting real-world heterogeneity in IgAN. Despite the differences in individual study methods, results across studies consistently found that lower proteinuria was associated with better kidney outcomes. Specifically, it was clearly established that <0.5 g/day achieved better outcomes than higher proteinuria thresholds.ConclusionThe evidence identified in this SLR affirms the updated KDIGO recommendation to achieve at least a proteinuria level of < 0.5 g/day.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251062821.